The assessment of blue lupine varieties according to productivity and adaptability in the conditions of Kirov region - A. P. Kislitsyna; F. A. Popov; E. V. Svetlakova; A. Yu. Sofronova (Аграрная наука Евро-Северо-Востока)
The article provides the results of the comparative study of grain productivity of 7 blue lupine (Lupinus angustifolius L.) varieties bred by the All-Russian Scientific Research Institute of Lupine in the conditions of Kirov region on sod-podzolic light loamy soil. It has been established that the yield of the seeds of blue lupine varied 1.5-2 times over the years of cultivation (2000-2022) depending on the weather conditions. Over 3 years on the average the varieties Bryansky kormovoy and Siderat were the most productive, 46-287 and 281 g/m2, respectively. Even in extremely unfavorable for blue lupine 2022 (by environment condition index of 62) these varieties significantly exceeded the control (Vitayz – 135.8 g/m2) in yield, by 72.9 and 61.1 %. The coefficient of adaptability of the varieties Siderat 46, Smena, Uzkolistny 53, Bryansky kormovoy was over 100 %. The productivity structure elements of blue lupine, namely: the number of beans per plant, the number of grains per bean and mass of 1000 seeds depended on hydrothermal conditions of the growing period. Under favorable conditions the number of beans per plant and the size of seeds increased. The number of grains per bean was the most stable indicator. The average duration of the growing period of lupine varieties was 84-91 days. In hot and dry weather of 2022 the ripening began 5-7 days earlier than long-time average annual periods. The varieties with highly developed side branching had a longer growing period – Bryansky kormovoy, Uzkolistny 53 and. Vitayz. During the year favorable by hydrothermal conditions the raw protein content in lupine seeds was 30.8-36.5 %. In unfavorable years it decreased by 20-45 % depending on the variety.